Asphaltene deposition and permeability impairment in shale reservoirs during CO2 huff-n-puff EOR process. (16th February 2020) - Li, Lei; Su, Yuliang; Lv, Yuting; Tu, Jiawei
Abstract: This study focuses on asphaltene deposition and permeability impairment in shale oil reservoirs during CO2 huff-n-puff process. Four different huff-n-puff cycles, two oil samples and five different injection pressures were applied in this study. The results showed that the asphaltene deposed the most in the first cycle. The permeability reduced by 30.2%, 50.25%, and 58.31% after the first, third, and seventh injection cycle, respectively. After seven cycles, the cumulative oil recovery without asphaltene deposition was about 21.5% higher than that with asphaltene deposition. The permeability impairment degree first increased and then decreased with the increase of injection pressure.